Big Data in cognitive sciences, didactics, education management and evidence-based education policy - Agatova, Olga (Nauka, 2024)
Тhe book reveals the methodology of big data analysis in the field of education – a new direction in science and practice. The book is addressed to education researchers who are interested in the application of data science in education and who are developing a data-driven approach in education and human development research. The book is also addressed to heads of educational organizations and heads of regional education systems, teachers and methodologists of various educational institutions. The book characterizes methods for analyzing educational data and data on education at the levels of educational analytics, institutional analytics, regional, regional (territorial) analytics. The content of the book reveals the development of information anthropology and cybersemiotics in expanding the arsenal of methods for analyzing human-generated educational data. Characterizes the development of the cognitive-didactic concept of digital educational environments in the interdisciplinary field of social cognitive science and data science. The book presents the results of research and development on changing the structure of competencies of pedagogical and managerial activities in the field of education, predicts changes in the system of qualifications in the context of the digital transformation of education.